Broadband measurement of Feibelman’s quantum surface response functions - Zeling Chen; Shu Yang; Zetao Xie; Jinbing Hu; Xudong Zhang; Yipu Xia; Yonggen Shen; Huirong Su; Maohai Xie; Thomas Christensen; Yi Yang (Proceedings of the National Academy of Sciences, 2025)
Feibelman d -parameter, a mesoscopic complement to the local bulk permittivity, describes quantum optical surface responses for interfaces, including nonlocality, spill-in and -out, and surface-enabled Landau damping. It has been incorporated into the macroscopic Maxwellian framework for convenient modeling and understanding of nanoscale electromagnetic phenomena, calling for the compilation of a d -parameter database for interfaces of interest in nano-optics. However, accurate first-principles calculations of d -parameters face computational challenges, whereas existing measurements of d -parameters are scarce and restricted to narrow spectral windows. We demonstrate a general broadband ellipsometric approach to measure d -parameters at a gold–air interface across the visible–ultraviolet regimes. Gold is found to spill-in and spill-out at different frequencies. We also observe gold’s Bennett mode, a surface-dipole resonance associated with a pole of the d -parameter, around 2.5 eV. Our measurements give rise to and are further validated by the passivity and Kramers–Kronig causality analysis of d -parameters. Our work advances the understanding of quantum surface response and may enable applications like enhanced electron field emission.